2015
DOI: 10.1039/c3ay42093k
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Stern–Volmer equation for studying the spectrofluorimetric quenching reaction of eosin with clindamycin hydrochloride in its pure form and pharmaceutical preparations

Abstract: A sensitive, selective, economic, and validated spectrofluorimetric method was developed for the determination of clindamycin hydrochloride in pharmaceutical preparations, depending on the reaction of its tertiary amino group with eosin Y.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(37 citation statements)
references
References 12 publications
0
37
0
Order By: Relevance
“…K sv values were evaluated from the slope of the plot (Geethanjali et al, 2015). Linearity of the plots was tested by calculation of the correlation coefficient (Gong & Zhu, 2013;Wahba, El-Enany & Belal, 2015).…”
Section: Fluorescence Spectroscopic Measurementsmentioning
confidence: 99%
“…K sv values were evaluated from the slope of the plot (Geethanjali et al, 2015). Linearity of the plots was tested by calculation of the correlation coefficient (Gong & Zhu, 2013;Wahba, El-Enany & Belal, 2015).…”
Section: Fluorescence Spectroscopic Measurementsmentioning
confidence: 99%
“…For clarification of possible binding modes between ET and SC4, thermodynamic parameters such as an enthalpy (ΔH), free energy (ΔG), and entropy (ΔS) data estimated from the following Eqs. 2-4 can be useful [31].…”
Section: Resultsmentioning
confidence: 99%
“…It is reported that Eosin Y fluorescence is quenched by the development of stable complex with cationic drugs under acidic conditions [29]. Eosin Y has been widely used to develop accurate and precise analytical methods for determination of several compounds of pharmaceutical importance through spectrofluorimetric and/or spectrophotometric measurement [23,27,[30][31][32][33][34][35].…”
Section: Resultsmentioning
confidence: 99%
“…Different analytical techniques were reported for their determination in different matrices including spectrophotometry [3][4][5][6][7][8], spectrofluorimetry [9][10][11], conductometry [12] and HPLC [13][14][15][16][17][18][19][20]. The complex formation that occurs between a lot of drugs and Eosin Y as an ion pairing agent has been considerably investigated using spectrophotometric and spectrofluorimetric assay of such drugs with or without using of metal [21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%